2017
DOI: 10.1093/mnras/stx2938
|View full text |Cite
|
Sign up to set email alerts
|

The temporal evolution of neutron-capture elements in the Galactic discs

Abstract: Important insights into the formation and evolution of the Galactic disc(s) are contained in the chemical compositions of stars. We analysed high-resolution and high signal to noise HARPS spectra of 79 solar twin stars in order to obtain precise determinations of their atmospheric parameters, ages (σ∼0.4 Gyr) and chemical abundances (σ<0.01 dex) of 12 neutron-capture elements (Sr, Y, Zr, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, and Dy). This valuable dataset allows us to study the [X/Fe]-age relations over a time inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 89 publications
11
112
0
6
Order By: Relevance
“…On the other hand, s-process elements are produced in low-mass AGB stars, hence we expect their abundance ratios to increase over time, this is observed in both Y and Ba in the thin disk, where Y has smaller metallicity scatter than Ba. A gradient reversal is observed for both elements in the thick disk (similar to e.g., Magrini et al 2018;Delgado Mena et al 2019;Spina et al 2018). Y (a light s-element) has higher abundance ratios compared to Ba (a heavy-s element) at a given age in the thick disk, this behaviour is also observed by Delgado Mena et al (2019).…”
Section: Age-abundance Trends By Metallicitysupporting
confidence: 73%
“…On the other hand, s-process elements are produced in low-mass AGB stars, hence we expect their abundance ratios to increase over time, this is observed in both Y and Ba in the thin disk, where Y has smaller metallicity scatter than Ba. A gradient reversal is observed for both elements in the thick disk (similar to e.g., Magrini et al 2018;Delgado Mena et al 2019;Spina et al 2018). Y (a light s-element) has higher abundance ratios compared to Ba (a heavy-s element) at a given age in the thick disk, this behaviour is also observed by Delgado Mena et al (2019).…”
Section: Age-abundance Trends By Metallicitysupporting
confidence: 73%
“…Follow-up observations are required to establish if the two stars also have two different architectures for their planetary systems. This is necessary to understand the origin of similar anomalies observed within other stellar associations (Spina et al 2015(Spina et al , 2018Tucci Maia et al 2014Teske et al 2015Oh et al 2018;Biazzo et al 2015;Saffe et al 2016Saffe et al , 2017, where the stars richer in refractory elements could also be the ones with a more chaotic architecture of their planetary systems.…”
Section: Discussionmentioning
confidence: 99%
“…Twin stars are objects with atmospheric parameters very similar to each other (e.g., ∆T eff 300 K and ∆log g 0.2 dex). It has been shown that a strictly differential line-by-line analysis of twin stars permits us to obtain differential abundances at the highest precision possible (e.g., Meléndez et al 2009;Bedell et al 2014Bedell et al , 2018Liu et al 2014;Spina et al 2018). In fact, when studying samples of twin stars, most of the systematic uncertainties that plague chemical abundance analyses are so similar among stars in the same binary pair that a strict differential line-by-line analysis cancels them out.…”
Section: Observations and Analysismentioning
confidence: 99%
“…The only outlier is the 6 Gyr-old KIC 10130039 which deviates from the expected P rot distribution by more than 50%. Thanks to our extensive radialvelocity monitoring together with detailed mapping of chemical anomalies and activity levels (dos Santos et al 2017;Spina et al 2018;Lorenzo-Oliveira et al 2018), we found that the stars placed considerably below the lower limit of rotation rate for a given age are, in fact, spectroscopic binaries. Two illustrative examples from dos Santos et al (2016) are the 4.0 and 7.2 Gyr-old SB HIP 19911 and 67620 which rotate at 4.1 km/s and 2.7 km/s level (P rot /sin i ∼12 and 20 days), respectively.…”
Section: Age-rotation Relationmentioning
confidence: 97%